Negotiating Colonial Memory and Cosmopolitan Intimacy: Gendered Subjectivity in Negeri Van Oranje’s Travel Narrative - Hapsari, Retno Tyas; Wibowo, Sarwo Ferdi; Muslimin, Muhammad Fadli (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2025)
This article examines the negotiation of colonial memory and cosmopolitan intimacy through the gendered subjectivity of Lintang in the novel Negeri Van Oranje. Drawing on Debbie Lisle’s framework of travel writing as a politically saturated genre, the study argues that the narrative does not merely celebrate transnational mobility or intercultural romance. Instead, it demonstrates how these experiences are Uiltered through a hierarchy of value where Dutch spaces, white masculinity, and metropolitan institutions remain privileged signs of aspiration. Methodologically, the research employs a qualitative interpretive design combining close reading and discourse analysis of scenes involving desire, education, and romantic attachment. The Uindings reveal three signiUicant patterns: Uirst, colonial desire is internalized prior to departure through Lintang’s aspirations for a Dutch education and a foreign husband; second, the Dutch social world is consistently narrated as morally and institutionally superior; and third, while interactions with Uigures like Arbenita and Jeroen introduce a fragile cosmopolitan ethic, it remains partial and conditional. The study concludes that the novel stages a